Synthesis and Characterisation of Fe(II) and Co(II) Complexes of 1-Azepinyl-3-(p-chlorophenyl-sulphonyl)-Urea - Qureshi, Rashida; Iqbal, S.A. (Asian Journal of Chemistry, 2010)
Complexes of glypinamide, 1-azepinyl-3-(p-chlorphenyl sulphonyl) urea, (parinase) with iron and cobalt were isolated with the composition (C13H17ClN3O3S)2M·2H2O (M ═ Fe or Co). Stability constants are calculated as 13.1010 and 12.0390 litres/mole and free energy changes are 17.6858 and 16.2527 Kcal./mole respectively for Fe and Co complexes.